A new analytical method to predict permeability properties of cementitious mortars: The impacts of pore structure evolutions and relative humidity variations. (March 2023) - Xiong, Qing Xiang; Tong, Liang-yu; Zhang, Zhidong; Shi, Caijun; Liu, Qing-feng
Abstract: This research develops analytical models in respectively describing the water vapour sorption isotherm and permeability properties based on a probabilistic method for pore size distribution and two transformation models for pore radius of cementitious mortars. By adopting the water vapour sorption model, the water saturation degree in cement-based materials is acquired and the influence of ions on water vapour sorption isotherm is modelled by introducing the water activity in thermodynamic equilibrium relation between liquid and vapour phases. The results reveal that the presence of ions increases the susceptibility of mortars to be water-saturated. Additionally, intrinsic permeability and relative permeability of mortars are predicted and the reliability of the permeability model is investigated. Finally, the permeability model is further extended considering the evolutions of pore structure and variations of relative humidity when cementitious mortars are subjected to precipitation and dissolution, which attempts to give an understanding of interactions between permeability and evolved pore structure that are not yet very commonly mentioned in literature. Modelling results show that both pore size distribution and relative humidity significantly affect permeability properties of mortars, especially when the water saturation degree is large. This research provides a novel insight into quantifying the permeability of mortars undergoing pore structure degradations. Highlights: An analytical permeability model is proposed based on pore size distribution. Permeability in unsaturated states is evaluated by introducing capillary interface in pore structure. Proposed permeability model is more appropriate for predicting intrinsic permeability from water intrusion. A dramatic decrease occurred in gas permeability when RH is less than 0.8.